The Effect of Morality, Compensation, and Professional Commitment to Fraudulent Financial Statements with Rationalization as an Intervening Variable Empirical Study on SKPD South Tangerang City - Anfusina, Min Sururi; Mappanyukki, Ratna (International Journal of Asian Social Science, 2020)
The case of fraud that occurred at LKPD in 2017 South Tangerang City has inflict a financial loss country up to 1.7 billion rupiahs, this incident proves that fraud is still a common practice even though it has violated the principles of accounting. This study aims to examine the effect of morality, compensation and professional commitment on fraudulent financial statement by rationalization as an intervening variable. The population in this study was all South Tangerang Regional Work Unit. The sampling technique used is Nonprobability Sampling with saturated sample method until 36 samples are obtained. The analysis in this study is structure equation modeling with the help of the Smartpls version 3.0 program. The results of the study concluded that morality has a significant negative effect on accounting report fraud while compensation and professional commitment does not significant effect on fradulent financial statemet and rationalization does not mediate the relationship of morality, compensation and professional commitment to fraudulent financial statement.